A multi‐level model of commitment‐based human resource practices on team performance: the team cognition model. (19th April 2019) - Liu, Min‐Shi; Wang, Mei‐Ling
Abstract : In recent years, many studies of competitive advantage have focused on how to efficiently develop team performance, such as by developing organizational interventions and team cognition structures that facilitate teamwork activities. This study focuses on the multi‐level effects of commitment‐based human resource (HR) practices, team cognition (awareness of expertise location and shared task understanding), teamwork processes, and team performance. A cross‐sectional study was conducted of 154 teams. This study has not only verified that organizational‐level commitment‐based HR practices rely on team‐level team cognition to influence team performance, but also verified that teamwork processes constitute an important mediating factor. In addition, commitment‐based HR practices give signals to team members expressing the team's values and the team's concern and support for members. This helps team members to understand the team's mission, goals, assessed strategies, which facilitates members' co‐ordination and integration of the team's mission and activities. Key points: This study has not only verified that organizational‐level commitment‐based HR practices rely on team‐level team cognition to influence team performance, but also verified that teamwork processes constitute an important mediating factor. In addition, commitment‐based HR practices give signals to team members expressing the team's values and the team's concern and support for members. This helps team members to understand the team's mission, goals, assessed strategies, which facilitates members' co‐ordination and integration of the team's mission and activities.